Beyond Governance: How Foreign Ownership and Commitment Transform Indonesia’s Carbon Reduction Efforts - Azhari, Intan Putri; Saraswati, Erwin; Sudarma, Made; Atmini, Sari (International Journal of Energy Economics and Policy, 2025)
Indonesia is still a major contributor to global carbon and the largest contributor in Southeast Asia. However, research on carbon emissions in the Indonesian corporate context remains limited. This study aims to investigate how climate governance might help lower carbon emissions by mediating the action of climate change commitment and the moderating effect of foreign ownership in carbon-intensive sectors in Indonesia. This study investigated 183 firm-year observations of energy, industry, and transportation companies listed on the Indonesian Stock Exchange (2015- 2023). Climate governance had a strong direct adverse impact on carbon emissions. Importantly, this relationship is significantly mediated by climate change commitment and moderated by foreign ownership. These findings suggest that policymakers should implement drivers that enhance climate governance among companies while simultaneously enforcing stronger climate commitments for effective carbon reduction strategies. This study is among the first to investigate the link between climate governance and carbon emissions from the prism of both mediation and moderation paths in an emerging economic environment, thus stressing how organizational commitment and ownership structure increase the effectiveness of climate governance.